« An Active and Defining Presence » : Le visible et le lisible dans l’œuvre collaborative de Robert Creeley - Barbara Montefalcone (Revue LISA)
Robert Creeley’s long-standing relationship with artists has gained him the name of the “artist’s poet”. By this definition Donald Sultan synthesizes Creeley’s specific poetic practice that accompanies most of the works of his artist friends. However, Creeley’s collaborative works almost never illustrate or interact with the visual on the same page. His poems are “echoes” of the paintings: they can exist with or without the visual. Creeley calls for “an active and defining presence” which works as a stimulus for his writing, and creates poetry that develops essentially from his aesthetic experiences. Through the analysis of “Inside my Head” (Anamorphosis, 1997), one of Creeley’s many collaborations with the Italian painter Francesco Clemente, we will try to show the specificity of the poet’s relationship with the visual. By establishing an analogy between Creeley’s writing and the nature of the line as it is defined by Jean-François Lyotard in his book Discours, Figure, we will show how, in Creeley’s collaborative projects, the visual and the verbal are related through rhythm.